The applied materiality for disclosure of information in the notes to the financial statements - Paulo Bekmessian Pinheiro; Sérgio de Iudícibus; Bruno Meirelles Salotti; Napoleão Verardi Galegale (Revista Eniac Pesquisa, 2017)
This research investigated how the materiality concept may be applied to the information disclosed in the notes to the Financial Statements. The study justifies itself to provide basis for the calculation of materiality to be applied on small, medium and large entities, in order to reduce to a minimum areas of inconsistency. After concluding that materiality can be used as a "tool" to decide which information should be disclosed in the notes to the Financial Statement, the study applies the materiality concept to an intentional sample, consisting on Public Companies from the Trucking Corporate Governance of the BM&FBOVESPA: JSL S.A. ("JSL") and Tegma Gestão e Logistica S.A. ("Tegma"). The results show that it is possible to use the materiality concept to the notes and the analyses indicate that between 33% and 27% of the information disclosed in the notes to the Financial Statements of JSL and Tegma could have been excluded based on the materiality calculated for the respective Companies.